Tindakan Sosial pada Pekerja Freelance: Studi Mahasiswa Institut Seni Indonesia Surakarta - Yuhastina Yuhastina; Okta Hadi Nurcahyono; Alfiana Umi Kholtsum (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
The increasing growth of creative economy actors has also encouraged high interest in jobs in the creative industry as freelance workers. This research is qualitative research with a phenomenological approach. The phenomenological approach aims to describe the social actions that occur in freelance workers at ISI Surakarta. This qualitative research uses the purposive sampling technique and data collection using in-depth interviews and portfolio observation. Data were analyzed using Miles and Huberman's analysis techniques, namely interactive data analysis and Max Weber's social action theory. Students who work freelance do so consciously with careful consideration of the consequences obtained from freelance work. Freelance work has also become a genetic and cultural heritage of ISI students themselves. The facts found in the field show that freelance work in the ISI Surakarta environment belongs to social acts of instrumental and traditional rationality.